2004
DOI: 10.3748/wjg.v10.i6.922
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between plasma D-dimer levels and clinicopathologic parameters in resectable colorectal cancer patients

Abstract: Hypercoagulation and higher fibrinolytic activities occur in patients with colorectal cancer. The operative trauma could enhance the fibrinolysis in the patients with colorectal cancer. The measurement of preoperative D-dimer levels is considered to be useful for predicting lymph node metastasis and stage of colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 17 publications
3
13
0
Order By: Relevance
“…[15] D-dimer levels found in our study were found to be close to the values found in the study by Dirix et al [9] and D-dimer levels in our study were higher than the levels found in studies done by Suega et al, [18] Ay et al [3] and Benoy et al [19] ( Table 2) In our study, mean plasma D-dimer levels were significantly higher in patients before surgery as compared to levels after surgery. This observation is similar to the findings of Xu G et al [20] who did a study on operable colorectal carcinoma patients, wherein it was observed that D-dimer levels were remarkably elevated pre-operatively and after surgery the D-dimer levels began to descend stepwise and after 2 weeks almost returned to control level. [20] This could be due to decrease in tumour burden following surgery.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…[15] D-dimer levels found in our study were found to be close to the values found in the study by Dirix et al [9] and D-dimer levels in our study were higher than the levels found in studies done by Suega et al, [18] Ay et al [3] and Benoy et al [19] ( Table 2) In our study, mean plasma D-dimer levels were significantly higher in patients before surgery as compared to levels after surgery. This observation is similar to the findings of Xu G et al [20] who did a study on operable colorectal carcinoma patients, wherein it was observed that D-dimer levels were remarkably elevated pre-operatively and after surgery the D-dimer levels began to descend stepwise and after 2 weeks almost returned to control level. [20] This could be due to decrease in tumour burden following surgery.…”
Section: Discussionsupporting
confidence: 80%
“…This observation is similar to the findings of Xu G et al [20] who did a study on operable colorectal carcinoma patients, wherein it was observed that D-dimer levels were remarkably elevated pre-operatively and after surgery the D-dimer levels began to descend stepwise and after 2 weeks almost returned to control level. [20] This could be due to decrease in tumour burden following surgery.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…[16,17] Subsequent studies have confirmed these findings. [18,19] Because the formation of deep vein thrombosis may affect the prognosis of patients, Stender et al further designed a prospective cohort study to eliminate the effect of this factor. [3] The results suggested that for colorectal cancer patients without deep vein thrombosis pre-or post-operatively, the 1-year survival rate of patients with preoperative plasma D-dimer levels above 0.3 mg/L was 78.1%.…”
Section: Discussionmentioning
confidence: 99%